Enterobacteria in Feedlot Waste and Runoff - Hrubant, G. R. (1972)
Samples of beef cattle feedlot waste (FLW), runoff from the pens, and water from a large drainage ditch at the feedlot were examined for Enterobacteriaceae. The drainage ditch receives the runoff but contains primarily subsurface drainage from fields on which FLW is spread for disposal. Planting and enrichment techniques with seven different media were used to isolate 553 cultures of enterobacteria. FLW contains about 50 million enterobacteria/g dry weight. More than 90% of these were Escherichia coli, none of which were enteropathogenic types as determined with multivalent sera. Citrobacter and Enterobacter cloacae were other organisms present in moderate numbers. Application of enrichment techniques broadened the spectrum of enterobacteria isolates to include the four Proteus spp., both Providencia spp., Klebsiella, Enterobacter aerogenes, Arizona, and a single isolate of Salmonella (serological group C(2)). Shigella was not isolated. The wide spectrum of enterobacteria in FLW may be a hazard if unsterilized waste is refed. Fewer enterobacteria occurred in the runoff and in the drainage ditch; the most numerous species in FLW also were most numerous at these sites. However, neither Salmonella nor Arizona was isolated from runoff or drainage-ditch waters.